The effect of C-coated alumina particles on properties of MgO–C refractories. Issue 20 (15th October 2022) - Hao, Xian; Gu, Qiang; Si, Yaochen; Ma, Weikui; Qian, Fan; Liu, Guoqi; Li, Hongxia
Abstract: In this study, carbon-coated α-Al2 O3 powder was prepared by two routes: a physical method and a chemical method. The obtained carbon-coated α-Al2 O3 powders were adopted to prepare MgO–C refractory materials for the purpose of regulating the in-situ synthesis of MgAl2 O4 . The effect of the carbon-coating α-Al2 O3 powder addition on the service behavior of MgO–C refractories was studied. The results show that both the physical and chemical methods for coating alpha-alumina particles could regulate the solid-phase formation of spinel in the magnesia carbon material, which weakened the solid-phase reaction of the spinel in the magnesia carbon material, thus reducing the volume expansion. Samples containing coated alpha Al2 O3 micropowder, prepared by the chemical method, presented the largest bulk density, the minimum apparent porosity, the largest cold and hot modulus of rupture, and the best thermal shock and corrosion resistance.